Analysis of Polymorphisms in Exons of the LYZ Gene and Effect on Growth Traits of Jinghai Yellow Chicken - Hou, Q.R.; Wang, J.Y.; Wang, H.H.; Li, Y.; Zhang, G.X.; Wei, Y.; Hassan (International Journal of Poultry Science, 2010)
Lysozyme plays important role in vertebrates and invertebrates for its unique protein structure and enzyme activity. In the present study, the potential physiological function of the chicken lysozyme gene (LYZ) was studied by SNP. 329 J+ line Jinghai Yellow chicken were involved in this experiment. To determine gene mutations, DNA analysis of the LYZ gene, including Single Strand Confirmation Polymorphism (SSCP) and direct DNA sequencing, was performed. Chicken Body Weight (BW) were analyzed by GLM of SAS software. DNA sequencing demonstrated a G111A transition of exon 1, a T1426C transition and a C1492T transition of exon 2, all of them were silent mutations that caused no alteration in amino acid sequence. Statistical analysis indicated that, AA and CC genotype related with high BW, TT and CN genotype contributed to low BW. Therefore, results suggested that there was a possibility of the LYZ gene SNPs acting as a genetic marker for growth traits of Jinghai Yellow chicken.